Penerapan Metode Card Sort untuk Meningkatkan Motivasi Belajar Fiqh Siswa Mts Nabil Husein Samarinda - Herwin, Herwin; Husin, Muhammad Said; Rahmawati, Indriana (Sultan Idris Journal of Psychology and Education, 2021)
Learning by using fun methods is expected to increase student motivation. Motivation has an important role in the learning process, with learning motivation students are expected to be able to understand the subject matter well. This study aims to determine the application of the card sort method to increase the motivation to learn fiqh in MTs Nabil Husein Samarinda. The research method was carried out using a qualitative approach, the sources of research data were school principals, Fiqh teachers, and students of MTs Nabil Husein Samarinda. The collection technique was carried out using interviews and documentation. The validity of the data was tested using a triangulation technique. The results of the research are as follows, 1) Selection of active and fun learning methods can increase student learning motivation, 2) Students are enthusiastic about learning using the card sort method, 3) The card sort method is utilized to the fullest in MTs Nabil Husein, 4) Use of the method card sort can help students to understand the lesson.